Magnetic resonance and ultrasound in achilles tendinopathy: Predictive role and response assessment to platelet-rich plasma and adipose-derived stromal vascular fraction injection. Issue 95 (October 2017) - Albano, Domenico; Messina, Carmelo; Usuelli, Federico Giuseppe; De Girolamo, Laura; Grassi, Miriam; Maccario, Camilla; Bignotti, Bianca; Tagliafico, Alberto; Sconfienza, Luca Maria
Highlights: Post procedure, increase of tendon thickness and Doppler signal was seen. Post procedure, no cross-sectional area, signal intensity, echotexture variation was seen. None of the pre-treatment parameters predicted treatment outcome. Abstract: Objective: To assess the correlation between magnetic resonance and ultrasound findings and clinical outcome after intratendinous injection of leucocyte-rich platelet-rich plasma or adipose-derived stromal vascular fraction in patients with non-insertional Achilles tendinopathy. Materials and methods: Forty-three patients (age: 47.8 ± 5.1, range 29–55) with unilateral or bilateral non-insertional Achilles tendinopathy (58 tendons overall) were randomly assigned to platelet-rich plasma (22 patients, 28 tendons) or adipose-derived stromal vascular fraction (21 patients, 30 tendons) injection group. All patients underwent magnetic resonance (tendon cross-sectional area, signal intensity, maximum anteroposterior thickness were measured), ultrasound (maximum anteroposterior thickness, power Doppler signal, ultrasound gray scale echotexture were measured), and visual analogue scale (VAS) pain evaluation at baseline and at six months from treatment. Wilcoxon, intraclass correlation coefficient, repeated measure ANOVA tests were used. Results: There was a significant (P < 0.001) decrease of mean VAS from pre-treatment (6.4 ± 1.4) to six-month evaluation (1.8 ± 1.7). Significant increase of tendon thickness measured using magnetic resonance (P = 0.013) and ultrasound (P = 0.012) and power Doppler signal (P = 0.027) was seen. There was no significant difference between pre- and post-treatment cross sectional area, signal intensity, and echotexture (P > 0.217). None of the pre-treatment parameters was a predictor of treatment outcome (P > 0.104). There was an excellent agreement between tendon thickness measurement between magnetic resonance and ultrasound (intraclass correlation coefficient = 0.986) Conclusions: Both treatments seem to allow for clinical benefit, associated to early slight increase of tendon size and power Doppler signal. Imaging cannot be used as a predictor of clinical outcome.